Rancang Bangun Alat Pengusit Hama Tikus Menggunakan Gelombang Ultrasonik: Rancang Bangun Alat Pengusir Hama Tikus Menggunakan Gelombang Ultrasonik - Triyani, Yuli; Styorini, wiwin; Widiasari, Cyntia (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
One of the agricultural problems in Indonesia is the rice field mouse pest. The problem is that controlling rat pests is done with chemicals that are not good for the rice field ecosystem, so it is necessary to prevent them by controlling rat pests that are more environmentally friendly, such as using ultrasonic waves. The rat repellent tool uses a NodeMCU ESP32 microcontroller with a PIR sensor to detect the presence of rats. The expulsion method uses ultrasonic waves which cause uncomfortable conditions for rat pests. The tool designed also uses an energy source from sunlight. The 50wp solar cell functions to convert sunlight energy into electrical energy. Then, energy is stored in the battery via the charger controller. The voltage produced by solar panels varies depending on the intensity of sunlight received with a maximum voltage of 22V. The PIR sensor can detect at a maximum distance of 8m at a beamwidth of 45°.